Comparative Genomics Analysis of Rice and Pineapple Contributes to Understand the Chromosome Number Reduction and Genomic Changes in Grasses - Wang, Jinpeng; Yu, Jiaxiang; Sun, Pengchuan; Li, Yuxian; Xia, Ruiyan; Liu, Yinzhe; Ma, Xuelian; Yu, Jigao; Yang, Nanshan; Lei, Tianyu; Wang, Zhenyi; Wang, Li; et al. (Frontiers in Genetics, 2016)
Rice is one of the most researched model plant, and has a genome structure most resembling that of the grass common ancestor after a grass common tetraploidization 100 million years ago. There has been a standing controversy whether there had been 5 or 7 basic chromosomes, before the tetraploidization, which were tackled but could not be well solved for the lacking of a sequenced and assembled outgroup plant to have a conservative genome structure. Recently, the availability of pineapple genome, which has not been subjected to the grass-common tetraploidization, provides a precious opportunity to solve the above controversy and to research into genome changes of rice and other grasses. Here, we performed a comparative genomics analysis of pineapple and rice, and found solid evidence that grass-common ancestor had 2n =2x =14 basic chromosomes before the tetraploidization and duplicated to 2n = 4x = 28 after the event. Moreover, we proposed that enormous gene missing from duplicated regions in rice should be explained by an allotetraploid produced by prominently divergent parental lines, rather than gene losses after their divergence. This means that genome fractionation might have occurred before the formation of the allotetraploid grass ancestor.